Teatro maldestro. Sul lavoro del regista Boris Nikitin - Müller-Schöll, Nikolaus (Kritik. Rivista di letteratura e critica culturale, 2024)
This Essay focuses on Boris Nikitin’s clumsy theatre, a theatre of revolt that brings into play nothing less than the play itself: the beginning and end of theatre, its conventions and even its rejection. The matrix and program of all Nikitin’s plays is fiction, plagiarism, fakery or fraud: on the stage reality and fiction merge and blur, disorienting the viewer. His performers are “expert of every day life” who on the stage inevitably become “expert of the stage”, triggering in the play with stage illusion a game of faith in representation in which the subject experiences together with the performer his own decentralization in a fictional process of discovery of his own hidden potentialities, of knowledge of self and reality.